Exploring the potential of anaerobic co-digestion of water hyacinth and cattle dung for enhanced biomethanation and techno-economic feasibility. (1st December 2022) - Ali, Sameh Samir; Elsamahy, Tamer; Abdelfattah, Abdallah; Mustafa, Ahmed M.; Khalil, Maha A.; Giannis Mastropetros, Savvas; Kornaros, Michael; Sun, Jianzhong; Azab, Maha
Graphical abstract: Highlights: Water hyacinth (WH) co-digested with cattle dung (CD) at various mixing ratios. Co-digestion is a key approach for enhanced biogas and methane (CH4 ) production. Co-digestion increased biogas and CH4 production by 111.3 and 173.6%, respectively. Co-digestion improved bacterial population as given by VIT® gene probe technology. WH/CD gate fee had a noticeable impact on co-digestion economic feasibility. Abstract: This study might be the first to explore the techno-economic implications of anaerobic co-digestion of water hyacinth (WH) and cattle dung (CD) to optimize their mixing ratios for enhancing methane (CH4 ) production. At a mixing ratio of 1:1, the maximum biogas and CH4 content was obtained. The co-digestion technique increased biogas and CH4 production by 111.3 and 173.6 %, respectively, over CD. On the 13 th day, the maximum daily CH4 content was 67.11 %. During 60 days of anaerobic digestion (AD), the pH and volatile fatty acids (VFAs) concentrations fluctuated in an inverse proportion. Before and after the AD, there was a significant decrease in carbon/nitrogen (C/N). The vermicon identification technology (VIT®) gene probe indicated that co-digestion improved microbial population analyses, particularly for CH4 -producing ( Euryarchaeota ) and acid-producing bacteria. According to the techno-economic evaluation, the maximum net energy content of biogas was 619.2 kWh/m 3 with a net profit of 110.4 USD/m 3 of substrate.